Developing Preservice Teachers’ Equity Consciousness and Equity Literacy - Bukko, Debra; Liu, Kimy (Frontiers in Education, 2021)
Teachers need the knowledge and dispositions to identify and dismantle barriers contributing to persistent educational inequity. This work begins by centering equity in teacher education with a focus on developing teachers’ critical consciousness of the systems of power and privilege in educational institutions. Utilizing equity-focused instruction and coaching, this study explored the development of preservice teachers’ Equity Consciousness and Equity Literacy knowledge and dispositions during a teaching-coaching-reflection transformative learning experience. Participants demonstrated increased Equity Consciousness and Equity Literacy, recognizing their assumptions about learners’ lived experiences and the funds of knowledge students bring to the learning environment. Findings from this empirical study indicate this approach contributes to the development of the equity-based dispositions essential to dismantling current educational barriers and replacing them with inclusive and empowering instructional practices.